Social Capital in the Asia Pacific 2020
DOI: 10.4324/9780429434471-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond 'know-what' and 'know-how' to 'know-who': enhancing human capital with social capital in an Australian start-up accelerator

Abstract: Beyond 'Know-What' and 'Know-How' to 'Know-Who'-Enhancing Human Capital with Social Capital in an Australian Start-up Accelerator This study investigates the enhancement of human capital with social capital in a start-up accelerator and how this integration affects the entrepreneurial learning experience. In particular, it examines the relative importance of the three components 'know-what', 'know-how' and 'know-who'. The study involved thematic analysis of semi-structured interviews with participants in an Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Nevertheless, this experience provided insights into important elements of entrepreneurship such as understanding customers, working in teams and relationships with suppliers. In more formal terms, these experiences made a significant contribution to the development of their human capital (Seet et al, 2018). Based on the analysis of extensive secondary data, Jayawarna et al (2014) found that human capital in childhood, adolescence and early adulthood was an important predictor of the likelihood that individuals would pursue a career in entrepreneurship.…”
Section: Prior Knowledge and Human Capitalmentioning
confidence: 99%
“…Nevertheless, this experience provided insights into important elements of entrepreneurship such as understanding customers, working in teams and relationships with suppliers. In more formal terms, these experiences made a significant contribution to the development of their human capital (Seet et al, 2018). Based on the analysis of extensive secondary data, Jayawarna et al (2014) found that human capital in childhood, adolescence and early adulthood was an important predictor of the likelihood that individuals would pursue a career in entrepreneurship.…”
Section: Prior Knowledge and Human Capitalmentioning
confidence: 99%